Integracja międzypokoleniowa przedszkolaków z seniorami cz. II. Opinie rodziców dzieci w wieku przedszkolnym = Intergenerational integration between preschool children and elderly people Part II. Opinions of preschool children's parents - Chrzan, Agnieszka; Bąk, Jadwiga; Świrszcz, Anna; Pietraszek, Agata; Charzyńska-Gula, Marianna; Kachaniuk, Hanna; Łuczyk, Marta (Journal of Education, Health and Sport, 2016)
Chrzan Agnieszka, Bąk Jadwiga, Świrszcz Anna, Pietraszek Agata, Charzyńska-Gula Marianna, Kachaniuk Hanna, Łuczyk Marta. Integracja międzypokoleniowa przedszkolaków z seniorami cz. II. Opinie rodziców dzieci w wieku przedszkolnym = Intergenerational integration between preschool children and elderly people Part II. Opinions of preschool children's parents. Journal of Education, Health and Sport. 2016;6(9):506-512. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154698 http://ojs.ukw.edu.pl/index.php/johs/article/view/3868 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 21.09.2016. Integracja międzypokoleniowa przedszkolaków z seniorami cz. II. Opinie rodziców dzieci w wieku przedszkolnym Intergenerational integration between preschool children and elderly people Part II. Opinions of preschool children's parents Agnieszka Chrzan1, Jadwiga Bąk1, Anna Świrszcz1, Agata Pietraszek2, Marianna Charzyńska-Gula3, Hanna Kachaniuk4, Marta Łuczyk2 1. SKN przy Katedrze Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2. Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3. Wydział Nauk Społecznych i Humanistycznych, Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu 4. Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Streszczenie. Cel pracy. Celem Pracy było poznanie opinii rodziców przedszkolaków na temat integracji międzypokoleniowej Metoda i materiał: Metodą badawczą był sondaż diagnostyczny z techniką ankiety. Badania przeprowadzono wśród 149 rodziców dzieci w wieku przedszkolnym z Lublina, Dęblina i Wadowic. Wyniki. Ponad 96% rodziców uważa, że dzieci powinny mieć kontakt z seniorami, natomiast 62% z nich sądzi, iż doświadczenie życiowe osób starszych jest bardzo przydatne dla młodego pokolenia. Co więcej 80,5% uznało ze organizowanie wspólnych zajęć seniorów z przedszkolakami to dobry pomysł. Niespełna 47% badanych uważało, że za czas poświęcony dzieciom, seniorzy powinni otrzymywać rekompensatę finansową z kolei 40,9% twierdziło przeciwnie. Rodzice oczekiwaliby od osób starszych w opiece nad ich pociechami realizacji takich zajęć jak: czytanie książek czy opowiadanie zdarzeń historycznych. Korzyści ze spotkań międzypokoleniowych według rodziców to przede wszystkim wartości edukacyjne. Wnioski. Warto popularyzować idee integracji międzypokoleniowej wśród społeczeństwa ze względu na liczne korzyści, jakie może przynieść zarówno seniorom jak i młodemu pokoleniu. Słowa kluczowe. starzenie się, integracja społeczna, rozwój dziecka, Abstract. Objective. The objective of the study was to get to know the opinions of preschool children's parents on intergenerational integration. Material and method. The diagnostic survey method was applied, together with the questionnaire technique. The survey was carried out among 149 parents of preschool children from Lublin, Dęblin and Wadowice. Results. Over 96% of the parents claim that children should have contact with seniors, while 62% of them think that the worldly experience of the elderly is very crucial for the young generation. Furthermore, 80.5% of the respondents stated that organising activities with the participation of seniors and preschool children was a good idea. Almost 47% of the surveyed claimed that seniors should receive payment for their time spent with children, while 40.9% stated otherwise. The parents would expect the following types of activities during meetings between seniors and children: reading books and telling stories about historical events. The benefits of intergenerational meetings according to the parents are most of all educational values. Conclusions. It is worth promoting the idea of intergenerational integration among society due to the numerous benefits that it may bring to the elderly and the young generation. Key words. aging, community integration, child development